Определение функций выживания и рисков коронарной смерти пациентов с инфарктом миокарда - Высоцкая, Елена Владимировна; Бых, А. И.; Никонов, В. В.; Нужнова, С. В. (Eastern-European Journal of Enterprise Technologies, 2009)
In the offered article authors are consider some aspects of determination functions of survival and risks of coronal death for patients with heart attack of myocardium. For determination of survival’s function and intensity of death it was offered to use such methods of statistical analysis, as tables of life times with a subsequent regressive analysis on the basis Coks non-parametric model